Efektivitas Penggunaan Whole Cell Dari Vibrio alginolyticus Sebagai Vaksin Oral Melalui Artemia Pada Benih Ikan Kerapu Tikus (Chromileptes altivelis) [Effectiveness Of Using Vibrio alginolyticus Whole Cell As Oralvaccine With Artemia To Humpback Grouper Fry (Chromileptes altivelis) ] - Hari Suprapto; Titik Desi Sukmawati (Jurnal Ilmiah Perikanan dan Kelautan, 2010)
Abstract Humpback grouper is the one of marine fish which can culture. The major problem of humpback grouper culture is high mortality at short time caused by pathogen infection include virus, bacterial, parasite and fungi. Pathogen infection at humpback grouper fry caused by bacterial from genus Vibrio spp. There was exceeding with vaccination. This research use oral vaccination with whole cell. Vibrio alginolyticus Whole cell as oral vaccine is suggested to prevent high mortality at humpback grouper fry. The purpose of this research is to know the successful about using Vibrio alginolyticus Whole Cell as Oral Vaccine to prevent high mortality of humpback grouper fry (Chromileptes altivelis). The experiment was done June until December 2009 at Gastroenteritis of Laboratory Tropical Disease Centre (TDC) of Airlangga University Surabaya and PT Benur Puteri Situbondo. The methods of this research is descriptive. Major parameter observed in this research was survival rate (%) and Relative Percentage Survival (RPS) of humpback grouper fry. Other parameter observed in this research was water quality include water temperature, pH, water salinity and Dissolved Oxygen (DO). Result of research shows that there are difference of survival rate between fingerling fish vaccination and fingerling fish non vaccination (control). Survival rate of humpback grouper fry which vaccine of Whole Cell 66 % even though survival rate of humpback grouper fry which non vaccine of Whole Cell (control) 46 %. Relative Percentage Survival (RPS) of humpback grouper fry which vaccine of Whole Cell 37 %. The value of RPS was resulted at this research shows low value so that must to perfecting and must to do again research. Water temperature 27-29oC, pH 7,3-7,5, water salinity 31-32 ppt and dissolved oxygen 5-6 ppm.